Changes in haematological and biochemical parameters in blood serum of horses during exposition to workload stress - Martin Massányi; Marko Halo, Jr.; Peter Massányi; Eva Mlyneková; Agnieszka Greń; Grzegorz Formicki; Marko Halo (Heliyon, 2022)
Health state of animals undergoing experimental procedures is an important topic nowadays, as even the small changes can influence the outcome of entire outcomes. Main aim of the study was to evaluate the influence of horse training on variety of blood parameters including mineral profile, energy profile, hepatic profile and haematology. In the experiment, the studied group of horses underwent training programme which consisted of transportation, lounging, riding, jumping, racing, treadmill training and shoeing. Blood samples were collected and later evaluated at the beginning, in the middle and at the end of 1-year lasting process. Our results show multiple significant changes in blood parameters, including changes to multiple minerals, such as Ca, K, Na as well as significant changes of total proteins, urea and certain hepatic profile parameters. Haematology results have also been affected in individual sample collections. Based on results of our study we can state that there have been changes to the internal milieu of the horse but also that there have not been any visible changes of the health status of the animals over the duration of the experiment.